PENINGKATAN MEMBACA PEMAHAMAN MELALUI STRATEGI DIRECT READING THINGKING ACTIVITIES (DRTA) PADA SISWA KELAS VA SDN BENDOGERIT 1 KOTA BLITAR - fatih, mohamad (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2019)
Purpose of this research is to improve the reading skills of the Indonesian subjects through remedial learning by using strategies DRTA on the subject of reading comprehension to conclude their story in a few sentences. Based on preliminary observations in learning reading comprehension teachers have not implemented the method and appropriate learning strategies. As a result, most students feel bored and tired in the following study. This type of research is Classroom Action Research (CAR), which consists of two cycles. Subjects were fifth grade students of SDN Bendogerit 1 Blitar City. Students learn completeness percentage at 34.05% pre-treatment, cycle I and cycle II 44.68% 89.36%. Given the importance of improving reading comprehension, it is advisable for teachers, students, the school and other researchers to work together in order to improve the quality of human resources in order to achieve a learning goal.